2014
DOI: 10.1080/10509674.2013.868388
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of High Level of Hostility Among Homeless Men on Parole

Abstract: High levels of hostility present a formidable challenge among homeless ex-offenders. This cross-sectional study assessed correlates of high levels of hostility using baseline data collected on recently-released male parolees (N=472; age 18-60) participating in a randomized trial focused on prevention of illicit drug use and recidivism. Predictors of high levels of hostility included greater depressive symptomatology, lower self-esteem, having a mother who was treated for alcohol/drugs, belonging to a gang, mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…There were differences the strength of the association depending on the measure of violence used. Unadjusted odds ratios were large and consistent for violent behaviour (OR 3.7, 95% CI 3.1–4.5, p < 0.001; i 2 = 34%, p = 0.163) [47], [48], [49], [50], [51]; in contrast there was no significant effect for violent offending (OR 1.0, 95% CI 0.4–2.7, p = 0.961; i 2 = 94%, p < 0.001) [45,[52], [53], [54], [55]]. One large cross-sectional survey of tertiary students found more perpetration of sexual exploitation/abuse among people using amphetamines [50]; another study of substance users found increased likelihood of intimate partner violence among those using amphetamines [56].…”
Section: Resultsmentioning
confidence: 93%
“…There were differences the strength of the association depending on the measure of violence used. Unadjusted odds ratios were large and consistent for violent behaviour (OR 3.7, 95% CI 3.1–4.5, p < 0.001; i 2 = 34%, p = 0.163) [47], [48], [49], [50], [51]; in contrast there was no significant effect for violent offending (OR 1.0, 95% CI 0.4–2.7, p = 0.961; i 2 = 94%, p < 0.001) [45,[52], [53], [54], [55]]. One large cross-sectional survey of tertiary students found more perpetration of sexual exploitation/abuse among people using amphetamines [50]; another study of substance users found increased likelihood of intimate partner violence among those using amphetamines [56].…”
Section: Resultsmentioning
confidence: 93%
“…Over the years, the CHSCP has guided studies on HIV and hepatitis risk, and health outcomes among drug-abusing and homeless adults (Nyamathi et al, 2007; Nyamathi, Hudson, Greengold, & Leake, 2012; Nyamathi, Stein, Dixon, Longshore, & Galaif, 2003; Stein & Nyamathi, 2004) and among ex-offenders (Nyamathi et al, in press). In this framework, an inclusion of antecedent factors such as type of facility incarcerated (jail vs prison), type of drug used and whether single or poly drug pattern, age, education, and mental health history) were of interest in our study.…”
Section: Introductionmentioning
confidence: 99%
“…Three (15%) of the included studies investigated associations between challenging behaviour and the use of MA (Bungay et al, 2006;Nyamathi et al, 2014aNyamathi et al, , 2014b. Behaviours described as having the Using methamphetamine to avoid victimization…”
Section: Behaviours That Have the Potential To Escalatementioning
confidence: 99%